Child feeding practices in a rural Western Kenya community - Grace M. Mbagaya (African Journal of Primary Health Care & Family Medicine, 2009)
Background: Breastfeeding is nearly universal in Kenya. However, supplementation of breast milk starts too early, thereby exposing the infants to diarrhoea and other infections. Despite the recommendation of the World Health Organization (WHO) of exclusive breastfeeding (EB) from birth to six months, EB is rare and poorly timed and complementary feeding (CF) practices are still common. The study describes feeding practices of children aged 0 to 24 months in the Mumias Division of the Kakamega district in Kenya. Method: Using a cross-sectional study, 180 mothers of infants/children were interviewed using a structured questionnaire. Data on socio-demographic characteristics, feeding practices and sources of information on the same were obtained from the mothers.